Penerapan Model Pembelajaran Discovery Learning dalam Meningkatkan Prestasi Belajar Matematika Siswa Sekolah Menengah Pertama - ROSMAWATI, EKA (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2018)
This study aims to improve the learning achievement of Mathematics through the application of discovery learning model. The data in this research consists of data of student learning activities, group work, and learning outcomes. Student learning activities measured are student attention, student learning interest, absorption of learning, student involvement in learning, and communication skills. Group work measured is group collaboration, mastery of discussion materials, ability to answer questions, and problem-solving skills. Learning outcomes were obtained from formative test scores independently. This classroom action research consists of 2 cycles, each cycle consisting of 3 meetings, and each meeting consists of planning stages, stages of action, observation and assessment stage, and reflection stage. The discussion technique used is qualitative decriptive. The results showed that the application of discovery learning model in learning athematics can improve student achievement. This increase can be seen from each cycle that changes significantly. The average of students' learning outcomes in the first cycle of meeting 1 was 57 with a completeness of 28%, increased at meeting 2 of 66 with 47% completeness, increased at meeting 3 by 70 with 59% completeness, then increased in cycle II of meeting 4 with average average 75 with 63% completeness, increased at meeting 5 of 79 with 84% completeness, increased at meeting 6 of 85 with 97% completeness. This increase in learning outcomes is parallel to the increase in learning activity gained on observation. In the first cycle of 28% both categorized and 72% enough, then increased in cycle II with 88% categorized very good, 11% good and 1% enough.